RELATIONSHIP BETWEEN ECUATORIAN STUDENT’S LEARNING STYLES AND ACADEMIC PERFOMANCE IN SOIL SCIENCE - Quichimbo Miguitama, Pablo Geovanny; Aguirre de Juana, Ángel Javier; Chérrez Chérrez, Giomara Michelle; Quichimbo Miguitama, Edison Andrés; Vanegas Cabrera, Raúl Alejandro; Jiménez Álvarez, Leticia Salomé (Ciencia del Suelo, 2018)
Nowadays, there has been increasing interest in topics related to education on soil science, however, topics about learning on this science have been poorly studied, particularly the relationship between learning styles and their academic performance have not yet been addressed in the literature. This study aimed to understand the different student learning styles of soil science and their effect on their academic performance at the career of Agronomy Engineering (University of Cuenca, Ecuador). For this purpose, this case-study research was based on the application of the CHAEA questionnaire in order to identify and relate the learning styles with the academic scores of a group of Ecuadorian students who receive introductory courses on soil science. Results demonstrated a general preference of students towards “pragmatic” and “activist” learning styles. In addition, marked differences by gender are clearly noticeable in terms of learning styles, being men more “pragmatic” than women, while women are more “activist” than men. Additionally, women revealed a tendency to be more “theoretical” and “reflective” than men. At last, results suggest that academic performance was not influenced by learning styles. However, in students who showed multimodal preferences of learning styles, their academic performance became higher. These results highlighted the relevance that education plans in soil science need to consider the diversity of students in terms on their learning style preferences.